Художні особливості геометричних килимів Київщини - Андріяшко, В. (Інститут народознавства НАН України, 2007)
The carpet-making of Kyiv region end of XIX – beginning of XX-th centuries developed in context of development of this type of the decorative art in the whole Ukraine and, in particular, in the Dnipro river area. An interesting and less researched phenomenon of art in the field of artistic textiles are geometric carpets of Kyiv region, particularly thous works, the ornament of which is based on the principle of non-background formation of the created motive. This means, that in the carpets of such a type the design of the ornamental motive and background are equivalent. In article, there was realized the analysis of composition decisions of the most typical samples of this carpets’ type from collection of the National historic ethnographic reserve “Pereyaslav”.